Human-computer interaction the fundamentals made easy! (Solic Tech, 2015)
Is Human Computer Interactions what you want to learn? Always wondered how one understand Computers proficiently? Does it interest you how HCI works? Purchase HCI to discover everything you need to know about it. Step by step to increase your Computer skill set. Learn how to operate computer systems socially. All your basic knowledge in one purchase!